Selection of antibacterial aptamers against Pseudomonas plecoglossicida and analysis on their potential binding proteins - Yunting Fan; Xiaojun Lin; Ying Tan; Mao Lin; Ming Fang; Lixing Huang; Qingpi Yan; Deji Gao; Jiaen Wang; Qibiao Weng; Jun Bo; Jiang Zheng (Aquaculture Reports)
Pseudomonas plecoglossicida is one of the main pathogens causing visceral white spot disease of the large yellow croaker (Pseudosciaena crocea). Although antibiotics are used to control P. plecoglossicida infections, the long-term and large-scale use of antibiotics can lead to the development of drug-resistant bacteria as well as environmental pollution. Therefore, it is necessary to develop novel antibacterial agents to treat P. plecoglossicida infections. In this study, we first developed a two-step-centrifugation method to isolate live and dead P. plecoglossicida cells. Subsequently, we used the Systematic Evolution of Ligands by Exponential Enrichment (SELEX) screening based on inhibition rate to directly isolate antibacterial aptamers from the random library without post-processing. We isolated five antibacterial aptamers, namely B1, B2, B4, B8, and B109, which showed good inhibitory effects against P. plecoglossicida. Among these, B4 showed the highest inhibitory effect (62.40 ± 4.17 %). Further analysis revealed no positive correlation between the inhibitory effect of aptamers and their affinities with the target bacterium. The B4- and B109-binding proteins were isolated from P. plecoglossicida by magnetic separation and sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE). Mass spectrometry analysis revealed that the 26 kDa ribosomal protein L2 was the probable B4-binding protein, while the 26 kDa ribosomal protein S3 and 75 kDa ribosomal protein S1 or succinate dehydrogenase flavoprotein subunit were the probable B109-binding proteins. Structural and subcellular localization analyses of these potential B4- and B109-binding proteins were also conducted. Our findings suggest that the inhibitory activity of the antibacterial aptamers against P. plecoglossicida may be mediated via their interaction with the ribosomal proteins, which can interfere with the protein synthesis process in the bacterium, affecting its growth. These findings provide the scientific basis for the development of functional antibacterial aptamers and the elucidation of their mechanisms of action.